Psychosis-linked Symptoms and Structural Brain Patterns in Cognitive Subgroups among Familial High-Risk Children in the ABCD Study - Türközer, Halide Bilge; Karcher, Nicole R; Clauss, Jacqueline; Nordentoft, Merete; Lewandowski, Kathryn E; Roffman, Joshua L; Öngür, Dost (medRxiv : the preprint server for health sciences, 2025)
Children at familial high risk for psychosis (FHR) are at substantially increased risk for psychotic disorders and other serious mental illnesses. Identifying risk subgroups within FHR youth may enhance prediction models to identify children at greatest risk for potential intervention. This study investigated psychosis-linked symptoms and structural brain patterns in neurocognitive subgroups among FHR children in the Adolescent Brain Cognitive Development (ABCD) Study using baseline, 2-year, and 4-year follow-up data. Among children with first- and second-degree family history of psychosis, neurocognitive subgroups were defined using NIH Toolbox Cognitive Battery baseline age-corrected total scores: children with low (FHR-LC, 0-33%, n=234), moderate (FHR-MC, 33-66%, n=261), and high (FHR-HC, 66-100%, n=277) cognitive performance. Psychiatric symptoms were assessed using Prodromal Questionnaire-Brief Child Version (PQ-BC) and Childhood Behavior Checklist (CBCL). Regional vulnerability indices (SSD-RVIs), which quantify the similarity of participants' structural brain patterns to the patterns found in adults with schizophrenia spectrum disorders, were calculated using cortical thickness measures following rigorous quality control. At baseline, FHR-LC had significantly higher PQ-BC and CBCL scores, and trend-level higher SSD-RVIs compared to FHR-HC. Longitudinally, PQ-BC and CBCL scores decreased with age across all FHR participants, while SSD-RVIs remained stable. No longitudinal cognitive subgroup-by-age interactions were observed, indicating that subgroup differences persisted over time. Children at FHR who have concurrent poor cognitive performance exhibit elevated and stable clinical and imaging psychosis risk markers. This suggests that they may represent a risk subgroup with elevated vulnerability, presenting an opportunity for early identification and intervention.